2022
DOI: 10.3390/molecules27248719
|View full text |Cite
|
Sign up to set email alerts
|

Acylhydrazones and Their Biological Activity: A Review

Abstract: Due to the structure of acylhydrazones both by the pharmacophore –CO–NH–N= group and by the different substituents present in the molecules of compounds of this class, various pharmacological activities were reported, including antitumor, antimicrobial, antiviral, antiparasitic, anti-inflammatory, immunomodulatory, antiedematous, antiglaucomatous, antidiabetic, antioxidant, and actions on the central nervous system and on the cardiovascular system. This fragment is found in the structure of several drugs used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 124 publications
0
14
0
Order By: Relevance
“…It has been reported in the literature that imine compounds are found in polar solvents such as dimethyl‐d6 sulfoxide in high proportion as E geometric isomer, while the proportion of Z geometric isomer increases in solvents of low polarity and in cases where intramolecular hydrogen bond formation is possible [33,34] . In the NMR spectra of such compounds, some signals appear as double sets [35–37] . When the 13 C NMR spectra were analyzed, it was observed that E/Z isomer was formed in compound 4 f and their ratio was E/Z =5/3 and E isomer was formed more because it is thermodynamically more stable.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been reported in the literature that imine compounds are found in polar solvents such as dimethyl‐d6 sulfoxide in high proportion as E geometric isomer, while the proportion of Z geometric isomer increases in solvents of low polarity and in cases where intramolecular hydrogen bond formation is possible [33,34] . In the NMR spectra of such compounds, some signals appear as double sets [35–37] . When the 13 C NMR spectra were analyzed, it was observed that E/Z isomer was formed in compound 4 f and their ratio was E/Z =5/3 and E isomer was formed more because it is thermodynamically more stable.…”
Section: Resultsmentioning
confidence: 98%
“…[33,34] In the NMR spectra of such compounds, some signals appear as double sets. [35][36][37] When the 13 C NMR spectra were analyzed, it was observed that E/Z isomer was formed in compound 4 f and their ratio was E/ Z = 5/3 and E isomer was formed more because it is thermodynamically more stable.…”
Section: Chemistrymentioning
confidence: 99%
“…Substituted benzene sulfonic acid derivatives, particularly benzene-sulfonyl hydrazones, have attracted more attention during the past decades because of their numerous potential uses in medicinal chemistry. [1][2] The pharmacological properties of benzene sulfonyl hydrazones, such as enzymatic modulation, [3][4] analgesia, [5] and antifungal [6] and antibacterial potential [7][8][9][10][11][12] are mainly well recognized. Besides that, it also contains a broad spectrum of bioactivity such as anticancer 1-3, [13][14][15][16][17][18][19][20][21] antidepressant properties [22][23] and activity against Alzheimer's disease [24][25][26] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Substituted benzene sulfonic acid derivatives, particularly benzene‐sulfonyl hydrazones, have attracted more attention during the past decades because of their numerous potential uses in medicinal chemistry [1–2] . The pharmacological properties of benzene sulfonyl hydrazones, such as enzymatic modulation, [3–4] analgesia, [5] and antifungal [6] and antibacterial potential [7–12] are mainly well recognized.…”
Section: Introductionmentioning
confidence: 99%
“…Acylhydrazones as reactive groups include both amide and imine structures and therefore can act as both hydrogen bond donors and acceptors. 12 Acylhydrazones have a strong coordination ability and a variety of coordination modes that allow flexibility in the orientation of the acylhydrazone structure in space, 13 so they can easily form stable hydrogen bonds or other interactions with biological targets, increasing the affinity for the receptor and thus affecting its biological activity. 14 The commercially available fungicide benquinox (Fig.…”
Section: Introductionmentioning
confidence: 99%